The crosstalk between parenchymal cells and macrophages: A keeper of tissue homeostasis - Chen, Yusi; Tang, Li (Frontiers in Immunology, 2022)
Nonparenchymal cells (NPCs) and parenchymal cells (PCs) collectively perform tissue-specific functions. PCs play significant roles and continuously adjust the intrinsic functions and metabolism of organs. Tissue-resident macrophages (TRMs) are crucial members of native NPCs in tissues and are essential for immune defense, tissue repair and development, and homeostasis maintenance. As a plastic-phenotypic and prevalent cluster of NPCs, TRMs dynamically assist PCs in functioning by producing cytokines, inflammatory and anti-inflammatory signals, growth factors, and proteolytic enzymes. Furthermore, the PCs of tissues modulate the functional activity and polarization of TRMs. Dysregulation of the PC‒TRM crosstalk axis profoundly impacts many essential physiological functions, including synaptogenesis, gastrointestinal motility and secretion, cardiac pulsation, gas exchange, blood filtration, and metabolic homeostasis. This review focuses on PC‒TRM crosstalk in mammalian vital tissues, along with their interactions with tissue homeostasis maintenance and disorders. Thus, this review highlights the fundamental biological significance of the regulatory network of PC‒TRM in tissue homeostasis.